Cell surface nucleolin interacts with and internalizes Bothrops asper Lys49 phospholipase A2 and mediates its toxic activity - Lina Massimino, Maria (2018)
Phospholipases A2 are a major component of snake venoms. Some of them cause severe muscle necrosis through an unknown mechanism. Phospholipid hydrolysis is a possible explanation of their toxic action, but catalytic and toxic properties of PLA2s are not directly connected. In addition, viperid venoms contain PLA2-like proteins, which are very toxic even if they lack catalytic activity due to a critical mutation in position 49. In this work, the PLA2-like Bothrops asper myotoxin-II, conjugated with the fluorophore TAMRA, was found to be internalized in mouse myotubes, and in RAW264.7 cells. Through experiments of protein fishing and mass spectrometry analysis, using biotinylated Mt-II as bait, we found fifteen proteins interacting with the toxin and among them nucleolin, a nucleolar protein present also on cell surface. By means of confocal microscopy, Mt-II and nucleolin were shown to colocalise, at 4 °C, on cell membrane where they form Congo-red sensitive assemblies, while at 37 °C, 20 minutes after the intoxication, they colocalise in intracellular spots going from plasmatic membrane to paranuclear and nuclear area. Finally, nucleolin antagonists were found to inhibit the Mt-II internalization and toxic activity and were used to identify the nucleolin regions involved in the interaction with the toxin